The effect of measurement error and land management covariates on machine learning derived digital soil maps - Malatji, Boitumelo Raymond (Stellenbosch : Stellenbosch University, 2025)
Malatji, Boitumelo Raymond. 2024. The effect of measurement error and land management covariates on machine learning derived digital soil maps. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131815